Koefisien Reliabilitas Pada Pengukuran Kepribadian yang Bersifat Multidimensi - , Wahyu Widhiarso ([Yogyakarta] : Fak. Psikologi Universitas Mercu Buana, 2009)
Psychological instruments which usually measure the underlying latent abilities or personality traits are called multidimensional measurements. The assumption of these measurements is that there are . two or more common factors that create interrelationship among the measured variables. Factor analysis is the method which proves the interrelationship of two or more factors. Researchers usually ignore the interrelationship found in these multidimensional measurements as they apply reliability formula, which is one-dimensional (I.e., Alpha Coefficient), to find out the reliability coefficient for multidimensional instruments used to measure personality traits. This article is aimed to answer the question if Alpha Coefficient is the right coefficient for one-dimensional measurement and if the Alpha Coefficient will underestimate or overestimate the reliability coefficient of the measurement. Some other reliability coefficients for multidimensional measurements are outlined.